(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2016)
Research of clasification of fish cyprinidae Family at Pangi river Pengumbuk village, Banyuasin regency Sumatera Selatan province on Agustus-September 2013. This research utilited the direct observation method by collecting fish samples which were caught by fisherman along Pengumbuk river. The result of the research geted 8 genera and 9 species. Key words : pengumbuk river, Classification, Cyprinidae, spesies.